2015
DOI: 10.1017/s1368980015001214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of anaemia in adolescents in Riyadh city, Kingdom of Saudi Arabia

Abstract: Objective: To determine the prevalence and correlates of anaemia in male and female adolescents in Riyadh, Kingdom of Saudi Arabia. Design: A cross-sectional community-based study. Setting: Five primary health-care centres in Riyadh. Subjects: We invited 203 male and 292 female adolescents aged 13-18 years for interview, anthropometric measurements and complete blood count. Blood Hb was measured with a Coulter Cellular Analysis System using the light scattering method. Results: Using the WHO cut-off of Hb < 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
4
43
1
2
Order By: Relevance
“…In the KSA, the prevalence of anemia in young people aged 15–21 years ranged from 16% to 34% with Hb < 12 g/dL [67,68]. Anemia was reported by Abalkhail et al in 20.5% of 800 Saudi students at 10.3%, 20.6%, and 24.6% for those aged 9–11, 12–14, and 15–21 years, respectively [67]; at the highest risk for developing anemia were those 12 years of age, of low social class, and menstruating girls.…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
See 1 more Smart Citation
“…In the KSA, the prevalence of anemia in young people aged 15–21 years ranged from 16% to 34% with Hb < 12 g/dL [67,68]. Anemia was reported by Abalkhail et al in 20.5% of 800 Saudi students at 10.3%, 20.6%, and 24.6% for those aged 9–11, 12–14, and 15–21 years, respectively [67]; at the highest risk for developing anemia were those 12 years of age, of low social class, and menstruating girls.…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Anemia was reported by Abalkhail et al in 20.5% of 800 Saudi students at 10.3%, 20.6%, and 24.6% for those aged 9–11, 12–14, and 15–21 years, respectively [67]; at the highest risk for developing anemia were those 12 years of age, of low social class, and menstruating girls. Similarly, in cross-sectional, community-based survey in the KSA of 203 males and 192 females aged 13–18 years, Alquaiz et al revealed that 16.7% of males and 34.2% of females had anemia with Hb < 12 g/dL [68]. This study showed significant associations between anemia and female gender, family history of IDA, overweight, no or little intake of fresh juices, and living in an apartment or a small house.…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…In Saudi Arabia, studies have estimated its prevalence among adults to range from 4% to 15% (8,9,10) . Nevertheless, a recent Saudi study (9) using a blood pressure (BP) of 140/90 as the diagnostic cut off point for HTN, reported that the prevalence rate for essential HTN was 11.8 % among the 2011 participants with a higher prevalence among males (73.6%) compared to (26.4%) females.…”
Section: Introductionmentioning
confidence: 99%
“…The expert panel reviewed international guidelines for the management of IDA prior to the consensus meeting and took into consideration available literature on IDA in the GCC region [3][4][5][6][7][9][10][11][12]. Different topics were chosen by reviewing the previously published literature and discussion among the authors.…”
Section: Evaluation Of Evidencementioning
confidence: 99%
“…In the UAE in 2014, IDA was diagnosed in 16% of healthy young adult women before marriage, but was rarely diagnosed in men (< 1%); similarly, ID was more common in women (22.0%) than in men (0.5%) [3]. In Saudi Arabia, anemia was reported in 34.2% of female adolescents and 40% of women of childbearing age, in 2015 [4,5]. In university students in Jeddah, Saudi Arabia, ID and IDA were observed in 25.9 and 23.9% of women, respectively [6].…”
Section: Introductionmentioning
confidence: 99%